Morphologic and Radiographic Effects of Acids on the Teeth: An in-Vitro Forensic Study - Kushdeep Kumar Gupta1, Abraham Johnson2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Teeth are generally considered as the most durable structures that resist physical, chemical and biological insults than skeletal tissue. Human identification through dental remains is of prime importance when the remains are found in chemical accidents such as acid attacks or uneventful accident in chemical industries, where soft tissues cannot provide reliable information. Proper examination and analysis of dental remains can provide vital information in forensic context.Objective: The present study aims to evaluate the morphology and radiographic features of teeth after exposure to highly acidic environment.Material and Method: A sample of total 80 extracted permanent teeth was used. Teeth were exposed to different acidic conditions like - 35% hydrochloric acid (30ml), 69% nitric acid (30ml), 98% sulphuric acid (30ml), 85% phosphoric acid (30ml) at intervals of 30 min, 1 hr, 2 hr, 4 hr, 8 hr, 16 hr and 24 hr. Before and after exposure to acids, radiographic and stereomicroscopic images were taken.Results: The effect of acids on teeth depends on various factors such as the type and concentration of the acid, and also the time period. The morphological and radiological changes normally includes - changes in dimensional stability, changes in texture and colour, changes in the appearance of fissures and cracks and also appearance of the fracture and fragmentation of the samples.Conclusion: Teeth can serve as a tool in identification of the victim when in contact with acidic condition. Hydrochloric acid, nitric acid and sulfuric acid cause changes in the teeth and it is possible to deduce the approximate duration for which a body has been immersed in acid based on the changes observed. The characteristics of teeth may be of assistance in cases of human identification where soft tissue features are unavailable.